2016
DOI: 10.1002/da.22489
|View full text |Cite
|
Sign up to set email alerts
|

Risk of New Onset Type Ii Dm in MDD Patients Receiving Second-Generation Antipsychotics Treatment: A Nationwide Cohort Study

Abstract: This study indicated that there is no significant difference in the risk of developing type II DM between MDD patients with and without SGA exposure. More studies focused on the benefit-risk assessment of SGA treatment in patients with MDD are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…Twenty studies reported the results of potential determinants other than the specific antipsychotic of the occurrence of diabetes (Supplementary Table 5) [ 14 17 , 19 28 , 30 , 31 , 33 , 36 38 ]. The factors most frequently reported as being associated with the occurrence of diabetes were age [ 14 16 , 21 , 36 38 ], nonwhite race [ 15 , 21 , 24 ], length of exposure [ 16 , 17 , 25 , 33 ], obesity/body mass index (BMI) [ 15 , 16 , 19 , 20 , 23 , 26 , 27 , 31 ], hypertension [ 19 , 20 , 26 , 27 , 36 ], dyslipidemia [ 20 , 21 , 26 , 36 , 37 ], and treatment with concomitant medications, such as beta-blockers [ 15 17 , 24 , 31 ]; thiazides [ 15 , 16 , 24 , 31 ]; angiotensin-converting enzyme inhibitors [ 24 ]; antihypertensives [ 38 ]; lipid-lowering drugs [ 38 ]; specific lipid-lowering drugs, including fibrates [ 31 ] and statins [ 15 , 31 ]; and selective serotonin reuptake inhibitors (SSRIs) [ 15 , 24 ]. Regarding the type of psychiatric diagnosis, some studies found an increased risk of occurrence of diabetes for those with schizophrenia [ 16 , 30 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty studies reported the results of potential determinants other than the specific antipsychotic of the occurrence of diabetes (Supplementary Table 5) [ 14 17 , 19 28 , 30 , 31 , 33 , 36 38 ]. The factors most frequently reported as being associated with the occurrence of diabetes were age [ 14 16 , 21 , 36 38 ], nonwhite race [ 15 , 21 , 24 ], length of exposure [ 16 , 17 , 25 , 33 ], obesity/body mass index (BMI) [ 15 , 16 , 19 , 20 , 23 , 26 , 27 , 31 ], hypertension [ 19 , 20 , 26 , 27 , 36 ], dyslipidemia [ 20 , 21 , 26 , 36 , 37 ], and treatment with concomitant medications, such as beta-blockers [ 15 17 , 24 , 31 ]; thiazides [ 15 , 16 , 24 , 31 ]; angiotensin-converting enzyme inhibitors [ 24 ]; antihypertensives [ 38 ]; lipid-lowering drugs [ 38 ]; specific lipid-lowering drugs, including fibrates [ 31 ] and statins [ 15 , 31 ]; and selective serotonin reuptake inhibitors (SSRIs) [ 15 , 24 ]. Regarding the type of psychiatric diagnosis, some studies found an increased risk of occurrence of diabetes for those with schizophrenia [ 16 , 30 ...…”
Section: Resultsmentioning
confidence: 99%
“…2 for binary outcomes and Supplementary Fig. 3 for time-to-event outcomes [35][36][37][38][39][40]. Among these latter studies, Rajkumar et al [39], in young adults with schizophrenia, showed that the three individual antipsychotics analyzed, namely, clozapine, olanzapine, and aripiprazole, were associated with a significantly increased likelihood of developing diabetes compared with antipsychotic-naïve patients.…”
Section: Studies Conducted In Adults Diabetesmentioning
confidence: 99%
See 1 more Smart Citation